Ангиоархитектоника глаза наземных позвоночных - Любомудров, А.П.; Лычковский, Л.М. (Вестник зоологии, 1974)
In the process of phylogeny of terrestrial vertebrates the angioarchitectonics of the eye undergoes less alterations than when changing the water environment for the air one. The morphology of the choriocapillary layer of the choroid proper, arrangement of its direct sources of blood flow and ways of blood outflow, which were composed distinctly enough already in the reptiles, manifest no considerable changes in the phylogeny of the vertebrates, inhabitants of the air environment. The progressive development of the vascular lumen of the eye frontal segment and differentiation of arterial ways of blood flow to the iris and ciliary body different in the birds and mammals are observed in the terrestrial vertebrates. The eye angioarchitectonics in some representatives of the mama mals differ mainly in the degree of development of the frontal ways of blood flow to the iris and ciliary body, in the degree of the retina vascularization and in peculiarities of the long posterior ciliary arteries ramification.